PENERAPAN MEDIA POP-UP BOOK MATERI RAGAM BUDAYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SD N 1 PRAMBANAN TAHUN AJARAN 2025/2026 - Rofisian, Nela; Sunaryo; Dwi Rahmawati, Niken; Huda, Saiful; Kusumawardani, Sani; Rahmawati, Silvia; Indah Lestari, Sri; Wuryanti, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low learning outcomes of Grade V students at SDN 1 Prambanan in Civics Education, particularly on the topic of Indonesian Cultural Diversity, served as the background of this study. In the pre-cycle stage, the classical completeness rate only reached 35.71% with an average score of 68.57, which was far below the Learning Objective Achievement Criteria (KKTP) of 75 and the minimum classical completeness target of 80%. Contributing factors included the dominance of lecturebased methods, the use of non-interactive media, and the absence of immediate feedback mechanisms for students. This study aimed to determine whether the implementation of Pop-Up Book media on Cultural Diversity material could improve the learning outcomes of Grade V students in Civics Education at SDN 1 Prambanan. This study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, carried out in two cycles. The Pop-Up Book media was integrated with the Problem Based Learning (PBL) model and the Gallery Walk strategy to create active, interactive, and meaningful learning experiences. Classical completeness increased from 35.71% in the pre-cycle to 57.14% in Cycle 1 with an average score of 75.00, and further improved to 82.14% in Cycle 2 with an average score of 83.21, surpassing the established success indicators. Improvements in Cycle 2, including media redesign using the one-page one-region principle, Gallery Walk Pop-Up activities, and a Culture Flash Quiz, significantly enhanced active student engagement. The implementation of Pop-Up Book media integrated with the PBL model and Gallery Walk strategy was proven effective in improving the learning outcomes of Grade V students in Civics Education at SDN 1 Prambanan.